Practical Approach to Open Source Intelligence (OSINT) : Volume 2. - Bhardwaj, Akashdeep. (Taylor & Francis Group, 2025)
This book offers a practical and in-depth exploration of Open-Source Intelligence (OSINT) tailored for cybersecurity professionals, digital investigators, and threat analysts.